Big Bird in China - Stone, Jon.; Bailey, Joseph A.; Muehl, Brian; Spinney, Caroll; Henson Associates; Jim Henson Productions; Public Broadcasting Service (U.S.); Sesame Workshop; Sony Music Entertainment, Inc.; Sony Wonder (Firm); Children's Television Workshop; Zhong yang dian shi tai (Beijing, China) ([United States] : Sony Music : Distributed by Sony Wonder, 2004)
Take a fantastic journey with Big Bird to the other side of the world to the magic and mystery of the Far East.
Title from container.
Originally broadcast as a television program in 1983.
Art director, Alan Compton ; music, Stephen Lawrence, Joe Raposo, Peter Schickele ; costume designer, Ramsey Mostoller.
Caroll Spinney as Big Bird, Brian Muehl as Barkley, and introducing Quyang Lien-Tze. Jim Henson's Sesame Street Muppets performed by Caroll Spinney, Brian Muehl, and Frank Oz.
MPAA rating: Not rated.
DVD.
Keywords: Big Bird (Fictitious character) -- Juvenile films; Big Bird (Fictitious character); China -- Juvenile films; China; Television programs for children; Children's films; Films for the hearing impaired